2019
DOI: 10.1016/j.saa.2018.09.055
|View full text |Cite
|
Sign up to set email alerts
|

High resolution spectroscopy on Te2: New lines for reference

Abstract: Ro-vibrational spectra of different electronic states of molecules are often used as absolute wavelength or frequency standards. These standards are also used to mitigate any slow drift of laser frequency during an experiment. In precision experiment, the two most commonly used molecular standards are iodine and tellurium, both are homo-nuclear diatomic molecules. The former is mostly used as standard for the long wavelength (600 − 900 nm) region, while the tellurium spectrum is widely used in short wavelength… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It allows the possibility of using it for metrological applications 19 and cavity‐quantum electrodynamics experiments 20 . The lines of tellurium molecules, which allow locking of an ECDL for precision spectroscopy were reported by Dutta et al 21 Recently, Dutta and Mukherjee 22 reported new found in the region close to 455 nm wavelength thereby obtained more than 100 new spectral lines high resolution modulation transfer spectroscopy on tellurium molecule. The linewidth of each of these peaks is about a few tens of MHz, making them suitable for laser frequency locking.…”
Section: Figurementioning
confidence: 99%
“…It allows the possibility of using it for metrological applications 19 and cavity‐quantum electrodynamics experiments 20 . The lines of tellurium molecules, which allow locking of an ECDL for precision spectroscopy were reported by Dutta et al 21 Recently, Dutta and Mukherjee 22 reported new found in the region close to 455 nm wavelength thereby obtained more than 100 new spectral lines high resolution modulation transfer spectroscopy on tellurium molecule. The linewidth of each of these peaks is about a few tens of MHz, making them suitable for laser frequency locking.…”
Section: Figurementioning
confidence: 99%
“…For the general case, this is not feasible using an acousto-optic modulator (AOM) due to inefficiencies at such large frequency shifts. 18 A well-established technique for generating a large frequency shift is to frequency-offset lock one laser to another, 19,20 as illustrated in Fig. 2.…”
Section: A Spectrometermentioning
confidence: 99%